Evaluating the Impact of Dissolved Oxygen and Aging on Dry-Hopped Aroma Stability in Beer. (3rd July 2019) - Barnette, Bradley M.; Shellhammer, Thomas H.
Abstract: It is generally recognized within the brewing industry that hop aroma and flavor in beer changes as beer ages post-packaging. Lager beer staling has been studied extensively, while dry-hopped beer has received limited attention. This study evaluated the impact of dissolved oxygen on the sensory and hop volatile profiles of dry-hopped beer during storage. Commercially-brewed dry-hopped beer was dosed with oxygen in a controlled fashion to create beers with a range of dissolved oxygen concentrations from approximately 40 to 250 μg/L 40 to 250 µg/L and then stored under chilled (3 °C) or accelerated (30 °C) storage conditions. Projective Mapping (Napping ® ) generated unique Euclidian configurations for each panelist, and ultra-flash profiling enriched the configurations with sensory descriptors. Sensory results identified storage temperature, used as a proxy for aging duration, as having the greatest effect on aroma during storage. Dissolved oxygen concentration was observed to have a lesser, but significant, impact at both high and low storage temperatures after only two weeks of aging. Higher temperature and dissolved oxygen concentrations resulted in decreased tropical, citrus, and hoppy characteristics and the expression of malty, dried fruit, and cardboard aromas. Hop derived monoterpenes were not significantly affected by treatment temperature or dissolved oxygen, suggesting stale character expression from alternate sources such as lipid oxidation or Strecker aldehydes formation.